Direct reprogramming of fibroblasts into endothelial cells capable of angiogenesis and reendothelialization in tissue-engineered vessels - Margariti, Andriana; Winkler, Bernhard; Karamariti, Eirini; Zampetaki, Anna; Tsai, Tsung-neng; Baban, Dilair; Ragoussis, Jiannis; Huang, Yi; Han, Jing-Dong J; Zeng, Lingfang; Hu, Yanhua; Xu, Qingbo (Proceedings of the National Academy of Sciences - PNAS, 2012)
The generation of induced pluripotent stem (iPS) cells is an important tool for regenerative medicine. However, the main restriction is the risk of tumor development. In this study we found that during the early stages of somatic cell reprogramming toward a pluripotent state, specific gene expression patterns are altered. Therefore, we developed a method to generate partial-iPS (PiPS) cells by transferring four reprogramming factors (OCT4, SOX2, KLF4, and c-MYC) to human fibroblasts for 4 d. PiPS cells did not form tumors in vivo and clearly displayed the potential to differentiate into endothelial cells (ECs) in response to defined media and culture conditions. To clarify the mechanism of PiPS cell differentiation into ECs, SET translocation (myeloid leukemia-associated) (SET) similar protein (SETSIP) was indentified to be induced during somatic cell reprogramming. Importantly, when PiPS cells were treated with VEGF, SETSIP was translocated to the cell nucleus, directly bound to the VE-cadherin promoter, increasing vascular endothelial-cadherin (VE-cadherin) expression levels and EC differentiation. Functionally, PiPS-ECs improved neovascularization and blood flow recovery in a hindlimb ischemic model. Furthermore, PiPS-ECs displayed good attachment, stabilization, patency, and typical vascular structure when seeded on decellularized vessel scaffolds. These findings indicate that reprogramming of fibroblasts into ECs via SETSIP and VEGF has a potential clinical application.